2016
DOI: 10.1134/s102144371603002x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of wheat germ agglutinin on the course of mitosis in the roots of Triticum aestivum seedlings exposed to cadmium

Abstract: Effect of pretreatment with 28 nM wheat germ agglutinin (WGA) on cell divisions in the root apical meristem of 4-day-old seedlings of wheat (Triticum aestivum L.), distribution of cells among mitotic phases, cadmium-induced disruptions of normal progression through mitosis, and activity of nucleolar organizer regions (NOR) of the chromosomes was studied after 7-h-long exposure to 1 mM cadmium acetate. Pretreatment with WGA has a pronounced protective effect on divisions of root meristem cells exposed to cadmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…This effect a time and a dose dependent. Similar effects of cadmium on the MI were reported in different plants such as in Lactuca sativa, Eruca sativa and Coriaudrum sativum (El-Ghamery et al, 2001), Phaseolus vulgaris (Çavusoğlu et al, 2009), in Lens culinaris (Kiran & Şahin, 2006), Pisum sativum (Fusconi et al, 2007), Triticum aestivum ( Bezrukova et al, 2016), Capsicum annuum (Aslam et al, 2014), Vigna radiatae (Munee et al, 2011), Vigna unguiculata (Thangaraja et al, 2013) Vicia faba (Li & Zheng, 1992;George, 2000;ElAshry et al, 2012 andArya &Mukherjea 2014), in Allium cepa (Zou et al, 2012;Wang et al, 2014and Nataliya, 2015 and Hordeum vulgare (Shi et al, 2017). The decline of MI suggested that the Cd could prevent cells from going into cell division (Unyayar et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…This effect a time and a dose dependent. Similar effects of cadmium on the MI were reported in different plants such as in Lactuca sativa, Eruca sativa and Coriaudrum sativum (El-Ghamery et al, 2001), Phaseolus vulgaris (Çavusoğlu et al, 2009), in Lens culinaris (Kiran & Şahin, 2006), Pisum sativum (Fusconi et al, 2007), Triticum aestivum ( Bezrukova et al, 2016), Capsicum annuum (Aslam et al, 2014), Vigna radiatae (Munee et al, 2011), Vigna unguiculata (Thangaraja et al, 2013) Vicia faba (Li & Zheng, 1992;George, 2000;ElAshry et al, 2012 andArya &Mukherjea 2014), in Allium cepa (Zou et al, 2012;Wang et al, 2014and Nataliya, 2015 and Hordeum vulgare (Shi et al, 2017). The decline of MI suggested that the Cd could prevent cells from going into cell division (Unyayar et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…Different types of mitotic abnormalities were observed in Nigella sativa L root tip cells after treatments with CdCl 2 . The variation in the percentages of chromosomal aberration in this study was recorded and the total abnormalities previously rapidly by increasing the concentration (El-Ashry et al, 2012;Zou et al, 2012;Thangaraja et al, 2013;Wang et al, 2014 andAslam et al, 2014;Nataliya, 2015;Bezrukova et al, 2016 andShi et al, 2017). In Nigella sativa L these types were: Irregular prophase, stickiness at different phases, disturbed metaphase, C-metaphase, bridges, forward chromosome and lagging in addition to other types recorded in low frequency in some treatments such as bi-nucleated cells and micronucleus.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations